Ser (um) expatriado, numa empresa: uma obrigação, uma distinção, um parêntese - Coelho, João Vasco (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2019)
The sense of ambivalence that tends to be associated with the representation of an expatriation as a contemporary work arrangement form used to anchor business internationalization processes, constitutes the problematizing axis of the research reported by this paper. Twenty-four individual experiences of expatriation observed in five different firms, born or located in Portugal, were studied. Analytical results suggest that performing work in an expatriation context can foster individual and social differentiation. Three types of expatriate experience are distinguished and described in detail.